Association between educational level and diabetes knowledge among older adults with type 2 diabetes in Bandung City: a cross-sectional study - Citra Windani Mambang Sari; Hartiah Haroen; Neti Juniarti; Lisda Amalia; Jerico Franciscus Pardosi (Intelektual Pustaka Media Utama, 2026)
Diabetes mellitus (DM) is a major non-communicable disease among older adults and a growing public health problem in Indonesia. Older people often have limited health literacy, which may affect their knowledge and self-management of DM. This study aimed to analyze the relationship between education level and knowledge about DM among the elderly in Bandung City, West Java. A descriptive cross-sectional study was conducted on 150 elderlies with type 2 DM using purposive sampling at primary health care facilities with high DM cases. Data were collected through structured interviews using a demographic questionnaire and a 15-item multiple-choice questionnaire on DM knowledge that had been tested for validity and reliability previously, adapted from an Indonesian diabetes self-management instrument. Knowledge scores were categorized into good and poor. Data were analyzed using the Chi-square test. Most respondents had an elementary or high-school education. The majority of the elderly with higher education levels had good knowledge about DM, while those with lower education levels tended to have poorer knowledge. There was a statistically significant association between education level and elderly knowledge about DM (p<0.001). Education level is significantly associated with DM knowledge among the elderly in Bandung. These findings highlight the need for a tailored continuity of care diabetes program, especially for the elderly with lower educational attainment, in order to improve self-management and glycemic control.